Eddy current separation technology for recycling printed circuit boards from crushed cell phones. (10th January 2017) - Li, Jia; Jiang, Yiqun; Xu, Zhenming
Abstract: Eddy Current Separation (ECS) is a classic method to separate light metal (aluminum) from plastic in the recycling industry. The aim of this paper is to present an innovative method that using the ECS to separate the printed circuit board (PCB) from the plastic generated from the crushed cell phone. A theoretical model of particle trajectory was established. On the basis of the computer simulation, it is found that ECS can be used to separate PCB from plastic with specific parameters. With the help of Design-Expert, the optimum separation conditions and selected operating parameters are analyzed with different velocities of feeding belt ( v ), rotating speeds of magnetic roller (ω), and radius of the particle ( R p ). The separation gets its optimal condition ( v  = 1.18 m/s, ω = 3000 rpm, R p  = 8.44 mm) by model calculation. A practical experiment showed that the separation efficiency reached 95.54%. Graphical abstract: Image 1 Highlights: The ECS was used to separate PCB particles from crushed cell phones. The trajectory of particle in ECS is simulated by MATLAB. Optimum design is developed to guide the further industrial application.